The political economy of work security and flexibility : Italy in comparative perspective / Fabio Berton, Matteo Richiardi and Stefano Sacchi. - Berton, Fabio; Richiardi, Matteo; Sacchi, Stefano (Policy, 2012)
This book casts light on the empirical relationship between labour market deregulation through non-standard contracts and the three main dimensions of worker security: employment, income and social security.